Modeling of Photovoltaic Solar Array under Different levels of partial shadow Conditions - Ali Mahmood, Humada; Fahmi, Samsuri; Hojabri, Mojgan; Mortaza, Mohamed; M. H., Sulaiman; Taha Hamad, Dakheel (2014)
Different methods of configuration have been formulated regarding photovoltaic solar power by employing several techniques. This has been done because of the varying conditions so that the loss of power can be minimized. The main factor which decreases energy output of the photovoltaic PV solar systems is partial shadowing. The way the energy output of partially shadowed arrays varies with the system configuration used, has been studied extensively. A huge degree of disorder still exists, particularly with respect to the best modularity grade for these systems. There are two distinct sub-divisions in the systems implemented in the reconfiguration mechanism: reconfigurable solar arrays, and a switching matrix to do a reconfiguration. Using different methods, the proportions of shadowing obstructions were noted to allow for calculation of the likely shadowing losses. The outcomes of this paper on modeling and monitoring are used to evaluate the photovoltaic system with respect to shadowing losses with different levels and their reliance on the system configuration are selected. It has been found that power loss because of varying conditions is majorly due to the decrease in radiance occurring on the photovoltaic array and can be avoided through selecting the suitable configuration and connection. The simulation results show that the output characteristics of the simulator presented better results with that proposed model.